2016
DOI: 10.1016/j.compind.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A framework for integrating syntax, semantics and pragmatics for computer-aided professional practice: With application of costing in construction industry

Abstract: Producing a bill of quantity is a knowledge-based, dynamic and collaborative process, and evolves with variances and current evidence. However, within the context of information system practice in BIM, knowledge of cost estimation has not been represented, nor has it been integrated into the processes based on BIM. This paper intends to establish an innovative means of taking data from the BIM linked to a project, and using it to create the necessary items for a bill of quantity that will enable cost estimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…They concluded that the proposed approach could be used to classify the building components to accelerate cost estimation. Xu et al (2016) introduced a framework based on semantic web ontology for taking data from BIM models and using it for generating the required items for a bill of quantity that enables cost estimation. Abanda et al (2017a, b) developed an ontology-based on new rules of measurement for quantity take-offs and cost estimation in the tendering stage of construction projects.…”
Section: Existing Studies On Bim-based Cost Estimationsmentioning
confidence: 99%
“…They concluded that the proposed approach could be used to classify the building components to accelerate cost estimation. Xu et al (2016) introduced a framework based on semantic web ontology for taking data from BIM models and using it for generating the required items for a bill of quantity that enables cost estimation. Abanda et al (2017a, b) developed an ontology-based on new rules of measurement for quantity take-offs and cost estimation in the tendering stage of construction projects.…”
Section: Existing Studies On Bim-based Cost Estimationsmentioning
confidence: 99%
“…Elsewhere, Haoues et al [103] suggest that compatibility and interoperability are key measures of system quality models and standards such as ISO 25010. Xu et al [104] create a prototype to collect data from BIM for generation of the item costs for the bill of quantity.…”
Section: Cluster a With The Focus On Bim Adoption And Interoperabilitymentioning
confidence: 99%
“…This dream of the development of computer systems requires at its heart that computers understand the workflow of professionals. Information has already been provided on the analysis of professional knowledge [32], and this paper instead concentrates on suggested solutions and authenticating results.…”
Section: Development Trends Of Computer Systemmentioning
confidence: 99%
“…However, at this point, no research has managed to merge the important aspects in one prototype. Despite many important pieces of research espousing the significance of a semantic underpinning in the domain [33,34], it is recognised that a synopsis is needed setting out all of the different views in relation to a system based on information, which includes compatibility (syntax), a description of pricing analysis (semantics), and precise information about the conditions surrounding the elements being assessed (pragmatics) [35]. Figure 1 illustrates the present system of quantity surveying.…”
Section: Proposed Solutionmentioning
confidence: 99%